Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2003)
This issue of Networks contains a varied collection of articles, ranging from research in elementary classrooms to investigations carried out by university teacher educators; in all, there is a concern on the part of the authors to improve the ways in which they fulfill their responsibilities and enthuse and challenge the students with whom they work.